1991
DOI: 10.1002/ceat.270140504
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized bed dryers: Dynamic modelling and control

Abstract: Fluidized bed drying finds important applications in the chemical industry on account of the following advantages: a) rapid exchange of heat and mass between drying media and particles yields the desired product quality and reduces the overall drying time and b) easy handling of feed and product. There is much scope for improving the existing modelling techniques as applied to predicting the performance characteristics of the dryers. This should provide a sound basis for the implementation of appropriate contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…They have extended their previous model for continuous and dynamic conditions and executed population balances. Panda and Rao [2] have attempted a review to provide the updated information on modelling and control of fluidized bed dryers [2]. They have reported that the moisture measurement poses additional problems for control and that there is need to improve control strategies in order to obtain optimal performance from dryers.…”
Section: Introductionmentioning
confidence: 99%
“…They have extended their previous model for continuous and dynamic conditions and executed population balances. Panda and Rao [2] have attempted a review to provide the updated information on modelling and control of fluidized bed dryers [2]. They have reported that the moisture measurement poses additional problems for control and that there is need to improve control strategies in order to obtain optimal performance from dryers.…”
Section: Introductionmentioning
confidence: 99%
“…Heat and mass transfer between the two phases are also assumed. Other authors have used a three-phase model that involves a dilute phase (bubbles), the interstitial gas, and the solid particles. Simplified models can be valid under some circumstances but not usually in many real situations.…”
Section: Introductionmentioning
confidence: 99%